Strong and Long-Lasting Antinociceptive and Anti-inflammatory Conjugate of Naturally Occurring Oleanolic Acid and Aspirin - Bednarczyk-Cwynar, Barbara; Wachowiak, Natalia; Szulc, Michal; Kamińska, Ewa; Bogacz, Anna; Bartkowiak-Wieczorek, Joanna; Zaprutko, Lucjusz; Mikolajczak, Przemyslaw L. (Frontiers in Pharmacology, 2016)
The conjugate 8 was obtained as a result of condensation of 3-hydroxyiminooleanolic acid morfolide (7) and aspirin in dioxane. Analgesic effect of OAO-ASA (8) for the range of doses 0.3 – 300.0 mg/kg (p.o.) was performed in mice using a hot plate test. Anti-inflammatory activity was assessed on carrageenan-induced paw edema in rats for the same range of doses. The conjugate OAO-ASA (8) did not significantly change locomotor activity of mice, therefore sedative properties of the compound should be excluded. The compound 8 proved a simple, proportional, dose-dependent analgesic action and expressed strong anti-inflammatory activity showing a reversed U-shaped, dose-dependent relation with its maximum at 30.0 mg/kg. After its combined administration with morphine (MF, 5.0 mg/kg, s.c.) the lowering of antinociceptive activity was found; however, the interaction with naloxone (NL, 3.0 mg/kg, s.c.) did not affect the antinociceptive effect of OAO-ASA (8), therefore its opioid mechanism of action should be rather excluded. After combined administration with acetylsalicylic acid (ASA, 300.0 mg/kg, p.o.) in hot-plate test, the examined compound 8 enhanced the antinociceptive activity in significant way. It also shows that rather the whole molecule is responsible for the antinociceptive and anti-inflammatory effect of the tested compound 8, however it cannot be excluded that the summarizing effect is produced by ASA released from the compound 8 and the rest of triterpene derivative. The occurrence of tolerance for triterpenic derivative 8 was not observed, since the analgesic and anti-inflammatory effects after chronic administration of the conjugate OAO-ASA (8) was on the same level as after its single treatment. It seemed that the anti-inflammatory mechanism of action of OAO-ASA (8) is not simple, even its chronic administration lowered both blood concentration of IL-6 and mRNA IL-6 expression. However, the effects of the conjugate OAO-ASA (8) on TNF-α level and mRNA expression were opposite. Moreover, compound 8 did not change unequivocally mRNA TLR1, and TLR3 expression. Concluding, the obtained results regarding the antinociceptive and anti-inflammatory activity of new conjugate of oleanolic acid oxime and acetylsalicylic acid (OAO-ASA 8) are very interesting, but for explanation of its mechanism of action, more detailed studies are necessary.